New combinations and re-lectotypification in the genus Imbralyx (Fabaceae: Millettieae) - Song, Zhu-Qiu (Phytotaxa, 2021)
Imbralyx R. Geesink (Fabaceae: Millettieae) was long recognized as part of the genus Fordia Hemsl. However, Imbralyx has a unique characteristic combination of characters within Millettieae and it can be readily distinguished from Fordia and other genera of the tribe, including transitional inflorescences to pseudoracemes, distinctly imbricate calyx lobes in buds, spindle-shaped flowerbuds, white flowers, distinct hypanthium, monadelphous stamens, and glabrous leaflets with raised nervation on both surfaces. Recent molecular evidence also suggested that Imbralyx should be treated as a genus distinct from Fordia, because the two genera were placed respectively in two different main subclades within the core Millettieae, i.e. Canavanine group and Non-canavanie group, which is consistent with previous chemical evidence. So far the genus Imbralyx comprises nine species and two varieties from Asia, but only one epithet has been definitely associated with the generic name. Therefore, ten new combinations in Imbralyx are proposed in this paper. Additionally, lectotypes are re-designated here for the two basionyms Millettia albiflora Prain and M. unifoliata Prain.